(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article confidently delves into the history of the origin (toponymy) and the pivotal role of Kotkor Aryk, which was presumably constructed in the second half of the 18th century using the ashar method, in ensuring the village of Beshik-Zhon had access to water for its livelihoods and agriculture.The article provides a definitive analysis of the significance of this irrigation structure in the lives of the local population and the crucial issues surrounding irrigation.The author meticulously compared information collected from informants among the local population with scientific literature. The historical significance of irrigation-related terms such as “aviz,” “murap,” “agat,” “ogaryk,” “alysh” and “bakan” has also been deciphered. The text also includes crucial data on the construction of new canals and irrigation networks that supplied water to six villages of the Beshik-Zhon kolkhoz м(Besh-Badam, Kalinin, 22nd Party Congress, Internat, Zhon, Lenin) during the Kyrgyz SSR period. It also covers the introduction of irrigated lands into agricultural use and the participation of kolkhoz workers in supplying water to irrigation structures.